Mediation in Teletandem: From face-to-face sessions to reflective journals - Evangelista, Maria Cristina Reckziegel Guedes; Salomão, Ana Cristina Biondo (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/Programa de Pós-Graduação em Língua e Literatura Alemã, 2019)
Abstract The collaborative context of language learning in Teletandem (Telles; Vassallo 2006) involves the principles of autonomy, reciprocity and separation of languages, as well as the mediation of the partnerships (in Vygotskian terms). This article aims to discuss the formats of teletandem mediation, by focusing on the strategies used to reconcile the management of interactions (Salomão 2008) through reflective journals in our specific educational context This qualitative investigation is based on the analysis of a corpus of reflective journals produced after teletandem sessions by Brazilian students and the feedback offered by the mediators. The Brazilian participants wrote journal entries after practicing teletandem with speakers of the following foreign languages: English, German, Italian, and Spanish. They address a wide range of topics, covering aspects of technology, foreign language learning, methodological issues, as well as comments on the relationship with their partners. The data suggest great potential of the journals and the feedback for participants, mediators and coordinators to evaluate specific issues of collaborative language learning in the teletandem, as well as other relevant aspects for the pedagogical supervision of the project.
Keywords: foreign language learning; Teletandem; mediation; reflective journals